Penerapan Model Pembelajaran Problem Based Learning (PBL) untuk Meningkatkan Minat Belajar Matematika Siswa Kelas XII SMA Negeri 1 Toma - Wawasan Darmawan Duha (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
The aim of this research is to increase students' interest in learning through the application of the Problem Based Learning (PBL) model. This research is classroom action research (PTK) which was carried out in two cycles. The research subjects were 20 class XII students of SMA Negeri 1 Toma. The data collection techniques used were learning implementation observation sheets, questionnaire sheets, and description tests. Next, analysis is carried out on the data that has been obtained. The research results show that applying the Problem Based Learning (PBL) model can increase students' interest in learning. This is proven by an increase in interest in learning from cycle I to cycle II. In cycle I, the percentage obtained was 71% in the